PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR BIOLOGI MATERI POKOK SISTEM GERAK PADA MANUSIA DI KELAS XI IPA SMA NEGERI 1 SIBABANGUN - Sri Rahmi Tanjung (PRODI PENDIDIKAN BIOLOGI, 2021)
The aim of this research was to know describing and to know whether there was a significant influence between using audio visual media on biology achievement in human motion system subject at the eleventh grade students of IPA mayor at SMA Negeri 1 Sibabangun. The approach of this research was quantitative by applying descriptive and experimental method. The total sample was 40 students. Based on descriptive analysis, using audio visual media had mean 91.40, it was categorized “very good”. Biology achievement in human motion system subject before using audio visual media had mean 56.10, it was categorized “low”. While biology achievement in human motion system subject after using audio visual media had mean 80.65, it was categorized “very good”. Based on inferential statistic, it could be gotten that tcount = 9.97, while ttable = 1.69 in error level 5%, confidence level 95%, df = N – 2 = 40 – 2 = 38. It could be seen that tcount was greater than ttable (9.97>1.69). The alternative hypothesis was accepted. It means there was a significant influence between using audio visual media on biology achievement in human motion system subject at the eleventh grade students of IPA mayor at SMA Negeri 1 Sibabangun.